Inhibitors such as staurosporine, H-7 or polymyxin B cannot be used in skeletal muscle to prove the role of protein kinase C on insulin action. Issue 5 (October 1992) - Gumà, Anna; Muñoz, Purificación; Camps, Marta; Testar, Xavier; Palacín, Manuel; Zorzano, Antonio
Abstract : The precise role of protein kinase C in insulin action in skeletal muscle is not well defined. Based on the fact that inhibitors of protein kinase C block some insulin effects, it has been concluded that some of the biological actions of insulin are mediated via protein kinase C. In this study, we present evidence that inhibitors of protein kinase C such as staurosporine, H-7 or polymyxin B cannot be used to ascertain the role of protein kinase C in skeletal muscle. This is based on the following experimental evidences: a) staurosporine, H-7 and polymyxin B markedly block in muscle the effect of insulin on System A transport activity; however, this effect of insulin is not mimicked in muscle by TPA-induced stimulation of protein kinase C, b) H-7 and polymyxin B block insulin action on System A transport activity in an additive manner to the inhibitory effect of phorbol esters, c) staurosporine, H-7 and polymyxin B block the effect of insulin on lactate production, a process that is activated by insulin and TPA in an additive fashion, and d) staurosporine completely blocks the tyrosine kinase activity of insulin receptors partially purified from rat skeletal muscle.